The Implications of Implementing the Global Minimum Tax on Fiscal Incentive Schemes in Indonesia - Aditya Pradana, Yudha; Adhari, Ade (Universitas Islam Negeri Alauddin Makassar, 2026)
The implementation of the Global Minimum Tax (GMT), initiated by the Organisation for Economic Co-operation and Development (OECD) and the G20, has brought significant changes to the effectiveness of fiscal incentive schemes in Indonesia, particularly those based on tax rate reductions, thereby requiring adjustments to national policies to remain aligned with global tax standards. This study aims to analyze the implications of the GMT’s implementation on the design and effectiveness of fiscal incentive schemes in Indonesia, while also assessing the suitability of the GMT policy in influencing the structuring of fiscal incentives and strengthening the government’s legal policy within the framework of tax policy reform. The research method used is normative legal research with a legislative approach, to examine the compatibility of GMT norms with the national legal system, as well as a conceptual approach to understand the paradigm shift from tax rate competition to global tax coordination. The research findings indicate that the top-up tax mechanism under the GMT regime significantly reduces the effectiveness of tariff-based fiscal incentives, thereby requiring Indonesia to restructure its fiscal incentive policies toward non-tariff incentives, enhanced legal certainty, and strengthened investment competitiveness. These findings confirm that the GMT policy is, in principle, aligned with the global tax reform agenda and reinforces the government’s legal policy direction in building a fair and equitable tax system, as well as promoting a restructuring of fiscal incentives that is more selective, transparent, and oriented toward investment quality and legal certainty, thereby providing conceptual and normative contributions to the development of national tax law and fiscal policy formulation practices in Indonesia.